Relationship Performance of Cylindrical Detention Pond (CDP) as Depression Storage and Runoff Reduction Under Fully Saturated Condition - Maseri, H.; Selaman, O. S.; Mannan, M. A.; Taib, S.N.L. (American Scientific Publishers, 2020)
Permeable pavements are a key Storm water management measure employed both to attenuate surface runoff in urban areas and to filter urban storm water pollutants. Existing permeable pavements (PP) are design with the specific percentage porosity whereby enabling excess rainwater to infiltrate through the system and acting as a depression storage at the same time. Depression storage basically refers to the volume of water trapped in the depression when the precipitation of a storm reaches the ground and filled up all the depression before it can flow over the surface. Cylindrical Detention Pond (CDP) is an alternative paving material that may alleviate many of the hydrological problems caused by urban runoff from developed areas. CDP consist of three basic component; top cover, bottom cover and hollow cylindrical at centre (300 mm thickness). The hollow cylindrical has approximate 50 percent porosity from the total solid of component, which is every 1 inch (25 mm) of pavement depth can hold 0.5 inches (12.5 mm) of rain in theoretical. In this study, the depression storage rate of CDP was investigated under three different rainfall intensity scenarios which are 77 mm/hr (low), 153 mm/hr (medium), and 230 mm/hr (heavy) respectively whereby it function to monitoring the analytical trend line. The experiment was conducted in model box in the laboratory under fully saturated condition. It found that the CDP can performed to detent the water until 180 min of excess rainfall for all 2 year ARI, 5 year ARI, 10 year ARI, 20 year ARI, 50 year ARI and 100 year ARI with different rates. CDP’s able to reduce the runoff up to 77% of the total rainfall volume. The result was proved the hollow cylindrical at centre of CDP very effective in runoff volume reduction according to the different ARI trend line projection.